Professor: agente de transformação social ou força motriz do sistema vigente? - Silva, Vera Regina da (2010)
Defining and comprehending the act of being a teacher is what motivates this research which approaches different aspects of their own social reversal: their work environment; their professional value; their teaching competence; their socio-political and pedagogical involvement; their physical and mental welfare and, consequently, their self-esteem and personal accomplishment. Based on this direct observation, as a manager of a public school for nine years, we refer to a group of teachers who work with Elementary Education at this same school, confronting the hypotheses we had with a substantial bibliographic theory from diverse authors. The most important finding was the interference of gender among male and female teachers that is clearly present in the occult curriculum of the school, determining the differences and personal and teaching behaviors. These peculiarities, empirically and scientifically proved, become very important so that the school managing group can better deal with these professionals and they can get to know themselves deeper and accept the differences between themselves and the other colleagues. Another important approach in this research is the stress which reaches a great number of teachers who undefended and without knowing the cause become victims of this pathology that sometimes makes them abandon their profession or work until the end of it without liveliness, without excitement, feeling extremely unhappy. In order to reach this analysis concerning the teachers personal and professional life, we laid emphasis on the current historical and social moment, its paradigms and its reflexes in the life of each individual. We also approached the contextualization of the school in society, discoursing with a greater emphasis, the state school of Rio Grande do Sul, with the demands and outrages, acting directly or indirectly in the teaching subjectivity.